MICRO TESE OUTCOMES IN PATIENTS WITH KLINEFELTER SYNDROME AT ANDROLOGY AND FERTILITY HOSPITAL OF HANOI (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the outcomes of microdissection testicular sperm extraction (Micro TESE) in patients with Klinefelter syndrome at Andrology and Fertility Hospital of Hanoi.Subject and methods: A retrospective descriptive study was conducted on 43 patients with Klinefelter syndrome who underwent Micro TESE at Andrology and Fertility Hospital of Hanoi from January 1, 2024, to August 30, 2025. Clinical characteristics, laboratory findings, sperm retrieval outcomes, IVF/ICSI results, and postoperative complications were collected and analyzed.Results: The mean age of the study population was 32.0 ± 4.84 years. The sperm retrieval rate using Micro TESE was 55.8% (24/43 cases). Among patients undergoing IVF/ICSI, the positive pregnancy rate was 70.6% and the cumulative live birth rate was 58.8%. Postoperative complications were generally mild, including nausea, wound pain, and scrotal hematoma, with no severe complications reported.Conclusion: Micro TESE combined with IVF/ICSI is an effective and safe approach for patients with Klinefelter syndrome, improving the chance of achieving fatherhood in this population.
Keywords: Klinefelter syndrome, Micro TESE, IVF/ICSI.